INTERACTION AND COORDINATION IN PERSONNEL POLICY IN THE PENITENTIAL SYSTEM (Bulletin of criminological association of Ukraine, 2025)
The article notes that the reform of the Ukrainian penitentiary system, which is taking place despite the full-scale military invasion of the Russian Federation into the territory of our state, is a very important step on the path of transforming the domestic law enforcement mechanism and bringing it into line with leading international standards. A separate significant issue on this path is overcoming a number of personnel problems and introducing an effective and stable mechanism for staffing the penitentiary system. After all, the quality of the personnel potential of the system directly and significantly determines its effectiveness. The emphasis is on the fact that the authorities understand the urgency of personnel issues in the penitentiary system and the need for their proper resolution. However, outlining the scale of personnel problems in the specified system and formulating priority tasks and steps to eliminate them, specialists bypass such important aspects as interaction and coordination, which are very significant factors that determine the effectiveness of the formation and implementation of the relevant personnel policy.
Keywords: interaction; coordination; personnel policy; personnel management; penitentiary system